Pharmacokinetics and Tissue Penetration of Linezolid following Multiple Oral Doses - Gee, Thekli (American Society for Microbiology, 2001)
The pharmacokinetics of multiple-dose linezolid were determined following administration of five 600-mg oral doses given every 12 h to each of six healthy male volunteers. Concentrations of the drug were determined in plasma and inflammatory blister fluid using high-pressure liquid chromatography. A mean peak concentration in plasma of 18.3 μg/ml (standard deviation [SD], 6.0) was attained at a mean time of 0.7 h (SD, 0.3) after the final dose. The penetration into the inflammatory fluid was 104% (SD, 20.7). A mean peak concentration of 16.4 μg/ml (SD, 10.6) was attained in the inflammatory fluid at 3 h (SD, 0.6) after the final dose. The elimination half-life from serum and inflammatory fluid was 4.9 (SD, 1.8) and 5.7 (SD, 1.7) h, respectively. The area under the concentration-time curve in plasma and blister fluid was 140.3 (SD, 73.1) and 155.3 (SD, 80.1) μg · h/ml, respectively. These data suggest that linezolid has good tissue penetration, and we can predict that it will be successful in the treatment of a variety of gram-positive infections.